Implication of Audit Reporting Lag on Financial Statements Restatement - Soetedjo, Soegeng; Putri, Mustika Suryaning (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to examine the effect of audit reporting log on financial statements restatement with firm size, big four public accounting firm, loss, and auditor switching as control variabels. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2014-2016. The sample used in 253 company data. The analysis technique used in this research is logistic regression. Data type is secondary data and processed with data processing software SPSS 20.0. The results found that audit reporting lag had positif effect on financial restatement.